Prenuptial Agreement Between Indonesia and South Korea Regulations - Asmarani, Abiyyah Indi; Hariyana, Trinas Dewi; Hasyim, Moch. Wachid; Al-Akiti, Muhammad Ayman (Jurnal Kajian Pembaruan Hukum, 2024)
This study examines the legal frameworks governing prenuptial agreements in Indonesia and South Korea, offering a comparative analysis between a developing and a developed nation in Asia. It explores cultural and societal attitudes that shape perceptions of such agreements in both jurisdictions. In South Korea, prenuptial agreements are also widely used. However, South Korea has one of the world’s lowest fertility rates, partly due to a declining interest in marriage. The research aims to evaluate regulatory frameworks, their impact on property arrangements, and the key similarities and differences in legal applications. Adopting study analyzes statutory laws, court decisions, expert opinions, and relevant literature. The comparative analysis highlights how both civil law systems address prenuptial agreements, focusing on property rights, joint assets, and marital obligations. Findings reveal that Indonesian regulations emphasize strict formality and limited scope, mainly addressing property, while South Korea permits broader flexibility and judicial discretion, including spousal support and child custody. The study concludes that while prenuptial agreements are legally binding in both countries, enforcement and societal acceptance differ significantly. It recommends harmonizing legal frameworks to ensure fairness and adaptability, especially in cross-national marriages. Indonesia could adopt South Korea’s flexible enforcement practices, while South Korea might benefit from stricter formal requirements for consistency. Such reforms could enhance the effectiveness of prenuptial agreements as tools for legal clarity and marital stability.